Iridium(I) Compounds as Prospective Anticancer Agents: Solution Chemistry, Antiproliferative Profiles and Protein Interactions for a Series of Iridium(I) N‐Heterocyclic Carbene Complexes. Issue 35 (22nd July 2016) - Gothe, Yvonne; Marzo, Tiziano; Messori, Luigi; Metzler‐Nolte, Nils
Abstract: A series of structurally related mono‐ and bis‐NHC–iridium(I) (NHC: N‐heterocyclic carbene) complexes have been investigated for their suitability as potential anticancer drugs. Their spectral behaviour in aqueous buffers under physiological‐like conditions and their cytotoxicity against the cancer cell lines MCF‐7 and HT‐29 are reported. Notably, almost all complexes exhibit significant cytotoxic effects towards both cancer cell lines. In general, the cationic bis‐carbene complexes show higher stability and greater anticancer activity than their neutral mono‐carbene analogues with IC50 values in the high nanomolar range. Furthermore, to gain initial mechanistic insight, the interactions of these iridium(I)–NHC complexes with two model proteins, namely lysozyme and cytochrome c, were explored by HR‐ESI‐MS analyses. The different protein metalation patterns of the complexes can be roughly classified into two distinct groups. Those interactions give us a first idea about the possible mechanism of action of this class of compounds. Overall, our findings show that iridium(I)–NHC complexes represent very interesting candidates for further development as new metal‐based anticancer drugs. Abstract : Iridium—a new player in the game : Iridium compounds in the oxidation state +I with NHC ligands show excellent antiproliferative activity against several cell lines (see figure). Mass spectrometry studies demonstrate that cellular proteins are likely targets of this new class of prospective anticancer agents.